Impact of Soaking Time at Room Temperature on the Physicochemical Properties of Maize and Potato Starch Granules. (23rd September 2018) - Alvarez‐Ramírez, José; Vernon‐Carter, Eduardo Jaime; Carrillo‐Navas, Hector; Meraz, Monica
Abstract : Starch‐rich foods such as cereals and tubers are the main source of energy in human diet, but are rarely consumed in their native form, requiring cooking to deem them more digestible. The soaking of starch‐rich matrices can reduce significantly energy consumption. In this work, native maize and potato starches are soaked in water (10 g/100 g water) at room temperature (20 °C) for up to 8 h, and the physicochemical changes (morphology, particle size, apparent viscosity, and crystallinity changes) are monitored for soaking times of 1, 2, 4, 6, and 8 h. Starch granules lose gradually birefringence, while the mean particle size increases by 7.0–9.0% by swelling effect. The apparent viscosity of the starch dispersion also increases about 5–7 times after 8 h of soaking. Differential scanning calorimetry shows that the enthalpy required for achieving complete gelatinization decreased by about 80–90% after the 8 h soaking treatment. Overall, the results indicated that soaking at room temperature offers an inexpensive mean for saving energy cost involved in starch gelatinization process. Abstract : Native maize and potato starches are soaked in water at room temperature, and the physicochemical changes are monitored. Differential scanning calorimetry shows that the enthalpy required for achieving complete gelatinization decreases by about 80–90% after 8 h soaking, indicating that soaking at room temperature offers an inexpensive mean for saving energy in starch gelatinization.